Externality Value of Waste Power Plant (PLTSa) in TPA Terjun Medan Marelan Using Benefit Transfer Method - Hidayah Fadli; Evi Gravitiani; Mugi Rahardjo (RIRAI Publisher, 2023)
In Indonesia, waste has become a national issue due to the old view that waste management is only collected, transferred, and disposed of in landfills. Several big cities in Indonesia also face the same problem. The open dumping of waste at the landfill in TPA Terjun Medan Marelan has resulted in negative environmental externalities that continue to get worse for the people living in the vicinity. The external costs of TPA Terjun Medan Marelan will be studied in this study. Residents living around the TPA are the research subjects. In this study, replacement costs and the cost of illness will be determined as a logical tool for calculating the total cost of externalities. Externality costs at the TPA Terjun Medan Marelan are calculated using benefit transfers. Given the difficulties and high costs associated with valuing actual costs, the benefit transfer method was developed as an alternative method for assessing externalities using scores from studies of similar circumstances or characteristics conducted elsewhere. This study focuses on estimating the costs of externalities related to the feasibility of a waste power plant (PLTSa) project using the benefit transfer method from the PLTSa project at TPA Benowo Surabaya, which is then applied to the PLTSa project plan at TPA Terjun Medan Marelan. The study found that the existence of the TPA Benowo Surabaya has a negative impact not only on the environment of the residents but also on its social and economic aspects. Then the researchers also found that there was also a negative impact from PLTSa in TPA Terjun Medan Marelan